Objective measurement of effective message through photograph among the public / Adzrool Idzwan Ismail - Ismail, Adzrool Idzwan (2010)
Photograph' to an extent is very close to visual representation, which consists of a part of an act of seeing which establishes places and subject matters in the surrounding world. What does visual really mean? Flow is visual measured? As an observer, how can we define whether the message and the meaning of a particular visual is delivered and understood along with the information it carries? Those three questions revolve the situation especially with the rapid growth of technology, which contributes to the development of human knowledge especially in the art industries. This thesis looks at the problems in understanding photography imageries and their impact in photography competition in Malaysia. It explores objective measurement of effective message through photograph among the public. These researches involve 3 different group of respondent. The first group is a general public in Klang Valley, the second group is a group of student from High Institute of Learning with Art & Design background, and the third group is a group of student from High Institute of Learning without Art & Design background. There are two levels of the research process: exploratory study and the descriptive study. The exploratory research is conducted to clarify unclear problems and is useful when research questions are not clear. Exploratory research was conducted by analyzing any existing studies on the subject, interviewed, unstructured focus group, by talking to experts, and also by informal investigation of the situation. In the pursuit to integrate the theories of sensual and perceptual process, two different approaches have been developed; subjective approach and objective approach to set up the effective instrument to achieve the aims and objective of this research.